INFLUENCE OF FLIPPED CLASSROOM TECHNIQUES ON ENGLISH LANGUAGE PROFICIENCY (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
A Flipped or inverted classroom is a relatively new educational practice. This educational method is widely acknowledged in most nations and implemented at the primary, secondary, and university levels. Researchers worldwide have focused on the perceptions, effectiveness, and obstacles of implementing flipped classrooms. This article is devoted to considering and providing a global perspective on how instructors and learners perceive the deployment of flipped classrooms, particularly in English language classrooms.